Considerations in Placement Decisions for Students With Extensive Support Needs: An Analysis of LRE Statements. (March 2019) - Kurth, Jennifer A.; Ruppar, Andrea L.; Toews, Samantha Gross; McCabe, Katie M.; McQueston, Jessica A.; Johnston, Russell
Special education consists of specially designed services available for students with disabilities, and should be available across placements. Students with the most significant disabilities continue to be taught in restrictive settings, despite accumulating evidence suggesting their special education services can be delivered effectively in general education settings. Every individualized education program (IEP) must contain a statement describing how the student will be provided a free and appropriate education in the least restrictive environment. The present study used content analysis to examine least restrictive environment statements of 88 students' IEPs to determine what factors, including supplementary aids and services, were considered in making placement decisions. We further analyzed the classes and activities in which students participated in general education settings. Findings reveal supplementary aids and services were not considered in placement decisions, although a number of factors centering on curricular considerations, environmental demands, student deficit, and personnel requirements were noted in making placement decisions. We further found students primarily participated in non-academic instruction while in general education settings. Implications for policy, practice, and research are included.